(untitled) (Bangladesh Rice Journal, 2018)
The study was conducted over all 42 upazilas of Chittagong region during 2016 using pre-tested semistructured questionnaire with a view to document the existing cropping patterns, cropping intensity and crop diversity in the region. The most dominant cropping pattern Boro−Fallow−T. Aman occupied about 23% of net cropped area (NCA) of the region with its distribution over 38 upazilas out 42. The second largest area, 19% of NCA, was covered by single T. Aman, which was spread out over 32 upazilas. A total of 93 cropping patterns were identified in the whole region under the present investigation. The highest number of cropping patterns was 28 in Naokhali sadar and the lowest was 4 in Begumganj of the same district. The lowest crop diversity index (CDI) was observed 0.135 in Chatkhil followed by 0.269 in Begumganj. The highest value of CDI was observed in Banshkhali, Chittagong and Noakhali sadar (around 0.95). The range of cropping intensity values was recorded 103−283%. The maximum value was for Kamalnagar upazila of Lakshmipur district and minimum for Chatkhil upazila of Noakhali district. As a whole the CDI of Chittagong region was 0.952 and the average cropping intensity at the regional level was 191%. Bangladesh Rice j. 2017, 21(2): 109-122